2009
DOI: 10.1111/j.1740-8709.2008.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive restraint, uncontrolled eating and emotional eating: correlations between parent and adolescent

Abstract: The purpose of this study was to examine, in a general population, the resemblance in eating behaviour between adolescents and their parents. This study was based on the first examination of a community-based epidemiological study in Northern France. Subjects were offspring aged 14-22 years (135 boys and 125 girls) and their parents (174 fathers and 205 mothers). The Three-Factor Eating Questionnaire Revised 18-item version (TFEQ-R18) identified three aspects of eating behaviour: cognitive restraint of eating,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 33 publications
5
41
0
Order By: Relevance
“…Several exploratory mechanisms have been proposed, including the use of eating as a source of comfort or the difficulty to distinguish hunger from other unpleasant internal states (38), possibly because of inappropriate learning experiences during childhood (39). In agreement with this notion, an association between EmE scores of daughters and mothers was evidenced (28). EmE and BED are interrelated (16,17).…”
Section: Eme Score and Weight Statussupporting
confidence: 62%
“…Several exploratory mechanisms have been proposed, including the use of eating as a source of comfort or the difficulty to distinguish hunger from other unpleasant internal states (38), possibly because of inappropriate learning experiences during childhood (39). In agreement with this notion, an association between EmE scores of daughters and mothers was evidenced (28). EmE and BED are interrelated (16,17).…”
Section: Eme Score and Weight Statussupporting
confidence: 62%
“…Research has also shown positive correlations between parents' emotional eating and adolescents' emotional eating (Lauzon-Guillain, et al, 2009;Snoek, Engels, Janssens, & van Strien, 2007), as well as between parents' emotional eating and preschoolers' eating in the absence of hunger (Blisset, Haycraft, & Farrow, 2010). Children's external eating tendencies, or eating in response to external food cues like the sight and smell of foods, are also related to those of their parents (Elfhag, Tynelius, & Rasmussen, 2010;Zocca, et al, 2010).…”
Section: Parental Eating Behaviormentioning
confidence: 99%
“…-Influence of family members: teenagers' imitation of their same-gender parent regarding nutritional behavior is more i.e., girls imitate their mothers and boys imitate their fathers in healthy and unhealthy nutritional behaviors (16). As teenagers grow older, the effect of parents on their nutritional behaviors changes due to the fact that pubescence is a complicated period of life associated with changes in effects of social factors.…”
Section: Interpersonal Determinant Factors Of Nutritional Behaviorsmentioning
confidence: 99%
“…This behavior is an unhealthy nutritional behavior and a factor in obesity (15). Since emotional eating occurs at improper mental conditions such as grieving, loneliness, or anxiety, it could also be an indicator of problems in the teenagers familial relationships (16).…”
Section: Intrapersonal Determinant Factors Of Nutritional Behaviorsmentioning
confidence: 99%